Short Communication: Dacini tribe's fruit fly species in Depok (Indonesia) with special reference to the abundance of orchard fly, Bactrocera dorsalis, for fruit pest controlling - QORY HERRAHMAWATI; RATNA YUNIATI; YASMAN YASMAN (Society for Indonesian Biodiversity, 2023)
Abstract. Herrahmawati Q, Yuniati R, Yasman. 2023. Short Communication: Dacini tribe's fruit fly species in Depok (Indonesia) with special reference to the abundance of orchard fly, Bactrocera dorsalis, for fruit pest controlling. Biodiversitas 24: 2447-2457. Knowledge of diversity and regularly monitoring pest insects in fields is crucial in crop protection and is key to effective pest control management. Our research group aims to map the species diversity of the Dacini tribe's fruit flies in Depok (Indonesia) using lure fruit fly traps and rearing fruit fly larvae from infected fruits. This preliminary study result is important for our next study to control fruit flies using tropical fruit extract as a natural lure. Four fruit flies were obtained from infected fruit purchased from a traditional fruit seller: Bactrocera dorsalis (Hendel 1912) and Bactrocera albistrigata (Meijere 1911) from Syzygium aqueum (Burm.fil.) Alston fruit and Bactrocera fuscitibia (Drew & Hancock 1994) and Bactrocera carambolae (Drew & Hancock 1994) from arum manis (Mangifera indica L.) fruit. Meanwhile, three fruit fly species were caught in lure traps using methyl eugenol: B. dorsalis, Bactrocera umbrosa (Fabricius 1805), and Bactrocera musae (Tryon 1927). Detailed morphological descriptions were provided for each species obtained. The B. dorsalis was the most abundant, while B. musae were the least abundant. This study's total number of individuals was 6,329 for B. dorsalis, 485 for B. umbrosa, and 34 for B. musae. The B. dorsalis is widely distributed in many tropical areas of Asia-Pacific and is considered an invasive species in Africa. Moreover, it is well known as one of the most important pest species within the Tephritidae family. While the remaining obtained fruit fly species have also been reported as pests, it is interesting to note that B. fuscitibia was reported as a non-pest species but was obtained from an infected mango fruit in this preliminary study. The B. musae was also reported for the first time in Depok, West Java Province, Indonesia.